Peran Guru Dalam Menanamkan Nilai-Nilai Religius Sebagai Pencegahan Degradasi Moral Di SD Labschool UPI Cibiru - Meylani Putri; Asep Rudi Nurjaman; Alya Rahmadiyani; Devinta Pradita Sari; Nisrina Nitakaina Kalusa (Universitas Islam Malang, 2024)
Character education, especially through religious education, is considered as one solution to overcome the increasingly widespread shift in morality among the younger generation. This research uses a descriptive qualitative approach by collecting primary data in the form of interviews to identify the role of teachers in preventing moral degradation. Teachers act as examples for students and are responsible for helping develop character in accordance with the principles of religious teachings. Some of the efforts made by teachers include getting into the habit of reading the Koran before learning, carrying out obligatory prayers in congregation, and implementing religious values ​​such as the dhuha prayer. Through these activities, it is hoped that students can gain inner peace, moral strength, and the ability to resist negative temptations that may come their way. Therefore, collaboration between schools, teachers and society is the key to creating a generation that has morals and noble character, as well as creating an environment that supports the holistic character formation of students. Keywords: Moral Degradation, Religious Value, Teacher’s Role.